Fluid simulation of dust-acoustic solitary waves in the presence of suprathermal particles: Application to the magnetosphere of Saturn - Singh, Kuldeep; Kakad, Amar; Kakad, Bharati; Kourakis, Ioannis (My University, 2022)
The observation of dust in the rings of Saturn by instruments on board the Voyager 1, Voyager 2, and Cassini missions triggered our interest in exploring the evolution of electrostatic dust acoustic waves (DAWs) in the Saturnian magnetospheric dusty plasma. The salient features of dust-acoustic electrostatic solitary waves have been examined by means of numerical simulations that adopted a fluid algorithm. We considered highly energetic non-Maxwellian ion and electron populations, in combination with inertial dust. The ions and electrons were modeled by kappa distributions to account for the long-tailed particle distribution featuring a strong suprathermal component. At equilibrium, the initial density perturbation in the dust density was used to trigger the evolution of DASWs propagating in non-Maxwellian dusty plasma. Our main focus is to determine the comprehensive role of the dust concentration and the suprathermal index (kappa) of the ion and electron populations in the generation and evolution of DASWs. These simulation results are thought to be relevant for (and applicable in) existing experimental data in space, especially in the magnetosphere of Saturn, but also in other planetary plasma environments that are presumably characterized by the presence of charged dust.
Keywords: plasmas – waves